2019
DOI: 10.1108/bfj-07-2018-0434
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of blueberry against hydrogen peroxide-induced oxidative stress in HEPG2 cells

Abstract: Purpose Blueberry contains bioactive compounds which are beneficial to organisms, such as phenolics and flavonoids. The purpose of this paper is to evaluate the potential protective effects of blueberry extracts (BE) on H2O2-induced HepG2 cells. Design/methodology/approach Cell protection was evaluated via the survivals of the cell. Reactive oxygen species (ROS) level, antioxidant enzyme and malondialdehyde (MDA) were detected. Western blot was carried out to analysis protein which was related to the cell ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Nevertheless, the use of these inhibitors often induced disturbances in the gastrointestinal tract, including flatulence, diarrhea and abdominal pain. In addition, the anti-inflammatory drugs, including aspirin and ibuprofen, are considered as antipyretic, analgesic and anti-inflammatory drugs (Wang et al, 2019). Although these antiinflammatory drugs can help treat many inflammatory diseases, they have side effects such as gastrointestinal injury, hepatotoxicity and osteoporosis (Ou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of these inhibitors often induced disturbances in the gastrointestinal tract, including flatulence, diarrhea and abdominal pain. In addition, the anti-inflammatory drugs, including aspirin and ibuprofen, are considered as antipyretic, analgesic and anti-inflammatory drugs (Wang et al, 2019). Although these antiinflammatory drugs can help treat many inflammatory diseases, they have side effects such as gastrointestinal injury, hepatotoxicity and osteoporosis (Ou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Bcl-2 family plays a pivotal role in the endogenous apoptosis pathway [ 47 ]. It was found that the ratio of Bax to Bcl-2 was the main factor determining the inhibitory effect on apoptosis [ 48 ]. An elevation in the Bax to Bcl-2 ratio modifies the potential of the mitochondrial membrane, stimulates the cytosolic release of cytochrome C, and triggers caspase-3 activation, ultimately leading to apoptosis [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“… 62 As a primary lipid oxidation product, MDA can aggravate membrane damage in senescence physiology and physiological resistance. 2 Intracellular MDA is a direct result of unsaturated fatty acid peroxidation in the membrane and is often regarded as a biomarker of oxidative stress. 24 Therefore, the MDA concentrations in the HepG2 cells were investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are produced during cellular oxygen metabolism and include superoxide anions (O 2 À ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (OH À ), and singlet oxygen ( 1 O 2 ). 1,2 ROS plays a vital role in the human physiological processes involved in cell differentiation, proliferation and migration, cell signaling, and homeostasis. [3][4][5] ROS may be benecial to human health at low concentrations by acting as a cellular signaling molecule to defend against infectious agents and mitogen response.…”
Section: Introductionmentioning
confidence: 99%